2000
DOI: 10.1562/0031-8655(2000)071<0029:tpboca>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Photochemical Behavior of Colchicone and Thiocolchicone

Abstract: The irradiation of colchicone 5 led to the formation of lumicolchicone 7. The same reaction cannot be obtained by using thiocolchicone 6 as substrate. Transient absorption spectroscopy of colchicone and beta-lumicolchicone showed that probably the photoisomerization occurred on colchicone in its first excited singlet state. The spectroscopic data are in agreement with the hypothesis that lumicolchicone was generated in the ground state from the S1 state of colchicone without the presence of any intermediate. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
(25 reference statements)
3
17
0
Order By: Relevance
“…These results are in perfect agreement with those obtained in colchicone. 25 Our observation is also in agreement with previous results, indicating that the photochemical conversion of colchicine to lumicolchicines does not involve or only partially involves triplet transients.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in perfect agreement with those obtained in colchicone. 25 Our observation is also in agreement with previous results, indicating that the photochemical conversion of colchicine to lumicolchicines does not involve or only partially involves triplet transients.…”
Section: Resultssupporting
confidence: 93%
“…The experimental instrumentation and data processing for femtosecond timeresolved transient absorption (TA) spectroscopy have been described in detail in previous papers. [25][26][27][28][29] Briefly, ultrashort pulses (duration ∼100 fs at 800 nm, repetition rate 1 kHz, energy 700 µJ/pulse) are produced by a Ti:sapphire-based laser system. The output of the amplifier is divided into two portions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of transport of lumicolchicines formed in the aerial part of the plant (flowers and leaves) to the corms and roots might also explain the presence of ␤-LC in these dark parts of the plants, although as noted above ␤-LC has been detected in the corms in the complete absence of light. Bussotti et al (31) recently reported that the non-nitrogen-containing 7-desacetamido-7-oxo-colchicine (colchicone), similar to colchicine photoisomerizes to ␤-lumicolchicone probably via its first excited singlet state.…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 This is important from a clinical point of view, as considerable amounts of lumicolchicine were found in clear-glass ampules filled with colchicine for intravenous injections. 32 Studies on colchicine photoisomerization have been reported, 30 , 32 34 but the influence of different substituents on colchicine photosensitivity has not been investigated. It has been reported that the colchiceine (C10-demethylated colchicine analogue) undergoes photoisomerization similarly as colchicine, whereas thiocolchicine (C10-thiomethyl analogue) is resistant to UV irradiation.…”
mentioning
confidence: 99%